Islamic architecture : form, function, and meaning - Hillenbrand, Robert (New York : Columbia University Press, 1994)
Embracing over a thousand years of history and an area stretching from the Atlantic to the borders of India and China, this is an unrivalled synthesis of the arts of Islamic civilization. From the death of the Prophet Muhammad to the present day, Robert Hillenbrand traces the evolution of an extraordinary range of art forms, including architecture, calligraphy, book illumination, painting, ceramics, glassware, textiles and metalwork.
Includes bibliographical references (p. 601-607) and indexes.
Keywords: Islamic architecture; Ceramic art history; Golden Age of Islam; Symbolism in architecture -- Islamic countries